Notificação de violência contra a mulher na rede pública de saúde de Goiânia- Goiás - Nogueira, Elza Gomes Finotti (2013)
Violence is a phenomenon that has always been part of human experience and has been emphasizing between the main causes of morbidity and mortality worldwide. Since 1993 the World Health Organization recognizes in violence a public health problem. In 2010, the Ministry of Health of Brazil recorded 27,176 notifications of cases of domestic violence, sexual and/or other violence. According to the data, the characteristics of victims of violence against women are: young adult, married or in a consensual union, resident of urban zone, higher education and white color. In relation to the likely perpetrator of the assault, mostly committed by a male person and that have closed relationship with the victim, provided that spouse or ex-spouse. Therefore, it should be noted the importance of the Brazilian public policies to combat violence against women and the institution of compulsory notification within the Health System in Brazil. The present study aimed to analyze the knowledge of professionals about the notification of cases of violence against women in the Municipal Health Secretariat of Goiânia-Goiás/Brazil. A qualitative study of exploratory type, whose study population consisted of professionals involved with attention to women in situation of violence and/or epidemiological surveillance of violence in three hierarchical levels of the Secretariat. It was used for data collection the interview and documentary research in written records and fingerprints of trainings addressing the subject of notification of violence against women. Considering the manifestations of the professionals interviewed in relation to the understanding of the role of the professional in the attention to women in situation of violence, one realizes that some procedures reported go beyond purely technical questions of assistance, especially to motivate to get support, receive, listen and observe, offer support and inspire confidence. Most professionals understand that the notification is mandatory, have epidemiological and purpose must be carried out by who does the attendance, even anonymously, evidencing compliance with what the law calls for the notification. As for the professionals ' knowledge about the reference flows and opposite-reference and existence of Protocol, it can be observed that there is a consensus, especially on the existence of the Protocol. Some understand the role of Network of Care for Children, Adolescents and Women in Situations of Violence, emphasizing the articulation of institutions, training of professionals and the support service of the Health Unit. Regarding training for the notification of cases of violence against women, professionals recognize the need of updates. With the documentary research found a significant quantitative educational events or courses, however, without subsidies to verify that meet National Policy for Continuing Education in Health (PNEPS), in force since 2004. In this way, it is considered that the training of professionals must fit the guidelines of PNEPS, and their records need to be qualified. Regarding the Network of Care for Children, Adolescents and Women in Situations of Violence is considered necessary a continuous, comprehensive disclosure of their actions to the professionals.